Quadratic Equations 4: Polynomial Equation

Download as pdf or txt
Download as pdf or txt
You are on page 1of 16

Quadratic equations 4

Objectives
In this chapter we should be able to
define quadratic equation.
learn about two types of quadratic equations.
solve quadratic equations by four methods.
by factorisation.
by completing the square.
by using formula.
by graphing.
solve equations reducible to quadratics.
understand theory of quadratic equation.
understand the nature of the roots of quadratic equation.
solve problems leading to quadratic equation given in verbal form.

It all started around 3000 BC with the Babylonians. They were one of the world’s first civilisations, and
came up with some great ideas like agriculture, irrigation and writing. They plotted the paths of the Sun, the
Moon and the Planets, and recorded them on clay tablets. To the Babylonians we owe the modern ideas of
angle, including the way that the circle is divided up into 360 degrees.
Let us suppose that you are a Babylonian farmer. Somewhere on your farm you have a square field on which
you grow some crop. What amount of your crop can you grow on the field? The amount of the crop that you
can grow is proportional to the area of the field, which in turn is proportional to the square of the length of
the side. Suppose you double the length of each side of the field, then you find that you can grow four times
as much of the crop as before. In mathematical terms, x is the length of the side of the field, m is the amount
of crop you can grow on a square field of side 1, and c is the amount of crop that you can grow, then
c = mx2. The First Quadratic Equation was born! Quadratic equations and areas are linked together like
brothers and sisters in the same family.
The study of quadratic equations is important because of its applications to parabolas and other conic
sections.

Zeros of polynomials
Consider the trinomial x2 + 3x + 2. Can this expression be made equal to zero by substituting some values
for x? Yes.
Putting x = − 1 we see
( −1)2 + (3( −1) + 2 = 1 − 3 + 2 = 0 , and putting x = – 2 we see ( −2)2 + 3( −2) + 2 = 4 − 6 + 2 = 0 . These values
of x = – 1 and − 2 are called zeros of the expression, as they make the expression zero.
Polynomial equation
When a polynomial is equated to zero or to any number, or in fact to any polynomial, it is called an equation.
In general we can write a polynomial equation as f(x) = 0

83
FXB0BAMM

Examples
1. x 2 + 8x = 0 2. x 2 + 3x + 2 = 0
2x + 3 5x + 3
3. x3 + 2x2 − 2x + 7 4. =
x + 4 3x + 5

Definition of quadratic equation


An equation of the form ax2 + bx + c = 0 where a, b, c are real numbers, a ≠ 0 is called a quadratic equation.
For example, x 2 − 5x + 4 = 0 and x2 – 14x + 45 = 0 are quadratic equations.

Types of quadratic equations


Quadratic equation is of two kinds, namely; ‘pure quadratic’ and ‘adfected quadratic’ (complete quadratic
equation).
1. A quadratic equation which contains only the second power of the unknown quantity (and not the first
power) is called a pure quadratic equation.
Example:
(i) 3x 2 = 147 (ii) 8x 2 − 47 = 100 + 5x 2
2. A quadratic equation which contains the second as well as the first power of the unknown quantity is
called an ‘adfected quadratic equation’.
Example:
(i) x 2 − 14x = 45 (ii) 2x2 + 7x + 6 = 0

General form or standard form


ax 2 + bx + c = 0 is known as the general form of a quadratic equation where a, b, c are real numbers and
a≠0.
1. When b = 0, it becomes a pure quadratic equation
2. When c = 0 and b ≠ 0 it is an adfected quadratic equation
3. When c ≠ 0 and b ≠ 0 it becomes an adfected quadratic equation

Roots
The values of the unknown quantity for which the equation is satisfied are called its roots and the process of
finding them is called solving the equation.
An important result to be kept in mind
If the product of two factors is zero, then at least one of them must be zero. i.e. if a.b = 0 either a = 0 or
b = 0 or both a and b = 0.
Proof
Consider the following possibilities.
1. If a = 0 then there is nothing to prove.
1
2. If a ≠ 0 then there exists a number
a
1 1
ab = 0 ⇒ (ab) = (0)
a a

84
FXB0BAMM

1
(Multiplying both sides by )
a
1 
∴  .a  .b = 0
a 
∴ 1b = 0
∴b=0
3. If a = 0 and b = 0 then there is nothing to prove. Hence, either a = 0 or b = 0 or both a and b are equal to
zero.

Solutions
A quadratic equation can be solved by any one of the following four ways.
(1) By factorization
(2) By completing the square
(3) By using formula
(4) By graphing.

Solution of pure quadratic equations


A pure quadratic equation can always be reduced to the simple form x2 = k and then the values of x can be
determined by taking the square root on both sides. The roots evidently will be + k or − k written
as ± k .
Example
1. 8x 2 − 47 = 100 + 5x 2
Solution
By transposing we get
8x 2 − 5x 2 = 100 + 47
3x 2 = 147
147
x2 = = 49
3
x = ±7
Note
By taking the square root on both sides we get ±x = ± 7. But + x = + 7 and – x = – 7 give the same value. Similarly
+ x = – 7 and – x = + 7, give the same value. Hence, we write only two values. i.e. x = + 7 and x = − 7 and not four.
2. (x + 5) (x − 5) = 39
Solution
x 2 − 25 = 39
x 2 = 64
x = ±8
x+2 x−2 5
3. + =
x−2 x+2 2
Solution
Multiplying both sides by 2(x 2 − 4)

85
FXB0BAMM

2(x + 2) 2 + 2(x − 2) 2 = 5(x 2 − 4)


2(x 2 + 4x + 4) + 2(x 2 − 4x + 4) = 5(x 2 − 4)
On simplification, we get
4x 2 + 16 = 5x 2 − 20 , x 2 = 36, x = ±6
4. (x + 3) (x + 4) + (x − 2) (x − 5) = 30
Solution
x 2 + 7x + 12 + x 2 − 7x + 10 = 30
2x 2 + 22 = 30
x2 = 4
x = ±2
2
5. 8x − 12x + 29 = 3x − 2
Solution
Squaring both sides
8x 2 − 12x + 29 = (3x − 2)2
8x 2 − 12x + 29 = 9x 2 − 12x + 4
x 2 = 25
x = ±5

Solution of Adfected Quadratic equations


Method of factorisation
Example
(i) Solve the equation, x 2 − 5x + 6 = 0 (ii) Solve, ab(x 2 + 1) = (a 2 + b2 )x
Solution Solution
Factorizing, we get ab(x 2 + 1) = (a 2 + b2 )x
(x − 3) (x − 2) = 0 Transposing
Now x − 3 = 0 gives x = 3 abx 2 − a 2 x − b2 x + ab = 0
or x − 2 = 0 gives x = 2 ax(bx − a) − b(bx − a) = 0
Therefore the roots are 3, 2 (bx − a) (ax − b) = 0
∴ bx − a = 0 or ax − b = 0
a b
∴ x = or x =
b a
a b
Hence, the roots are ,
b a

Method of completing the square


The general form of a quadratic equation is
ax 2 + bx + c = 0
ax 2 + bx = −c
Dividing by ‘a’ (since a ≠ 0)
b c
x 2 + .x = −
a a

86
FXB0BAMM

2
 b  b b2 c
x 2 + 2.x.   + 2 = 2 −
 2a  4a 4a a
2
b2  b  b2 − 4ac
adding to both sides,  x +  =
4a 2  2a  4a 2
b b 2 − 4ac
Taking square root, x + =±
2a 2a
− b ± b2 − 4ac
∴x =
2a
− b + b2 − 4ac − b − b2 − 4ac
Thus, the roots are and
2a 2a
Example
1. Solve 2x 2 − 7x + 6 = 0
Solution
Here, a = 2, b = −7, c = 6
7 ± ( −7)2 − 4(2)(6)
∴x =
2.2
7 ± 49 − 48 7 ± 1
= =
4 4
7 +1 8
= = =2
4 4
7 −1 3
= =
4 2
2. Solve x2 – 5x + 6 = 0 by completing square.
Solution
2 2
5  5  5
x 2 − 2.x. +   = −6 +  
2 2 2
2
 5 25 −24 + 25 1
 x −  = −6 + = =
 2 4 4 4
5 1
x− =±
2 2
5 1
x= ±
2 2
5 1
x = + = 3 or
2 2
5 1
x= − =2
2 2
3. Solve by completing the square (x + 4)(x + 5) = 3(x + 1)(x + 2) + 2x
Solution
(x + 4)(x + 5) = 3(x + 1)(x + 2) + 2x
x 2 + 9x + 20 = 3x 2 + 9x + 6 + 2x
2x 2 + 2x − 14 = 0

87
FXB0BAMM

x2 + x − 7 = 0
2 2
1 1 1
x 2 + 2.x. +   = 7 +  
2 2 2
2
 1 1 29
x +  = 7 + =
 2 4 4
1 29
x+ =±
2 2
1 29 1 29
x=− + or − −
2 2 2 2

Solving a quadratic equation using the formula


While solving the quadratic equation, ax2 + bx + c = 0, by completing square we got the result as
− b ± b 2 − 4ac
x= … (A)
2a
− b + b 2 − 4ac
i.e. x = … (1)
2a
− b − b2 − 4ac
or x = … (2)
2a
a, b, c of the above equation may be positive or negative quantities and hence we may regard the above as
formulae, from which we get the roots of any equation by substituting the value of a, b, c from the given
equation.
−(Coef of x) ± (Coef of x) 2 − 4 ( Coef of x 2 ) (absolute term)
The formula may be written as x =
2 ( Coef of x 2 )

Worked examples
Solve using the formula
1. 3x 2 = 2x + 1
Solution
3x 2 = 2x + 1
3x 2 − 2x − 1 = 0
a=3 b=–2 c=–1
Therefore;
− b ± b 2 − 4ac
x=
2a
2 ± 4 + 12
x=
6
2±4
x=
6
2+4 6 2 − 4 −2 1
x= = = 1 or x = = =−
6 6 6 6 3

88
FXB0BAMM

2. x2 − x − 1 = 0
Solution
x2 − x − 1 = 0
Here, a = 1 b=–1 c=–1
− b ± b 2 − 4ac
Hence, x =
2a
1± 1+ 4 1± 5
x= =
2 2
1+ 5 1− 5
i.e. x = or
2 2

Equations reducible to a quadratic equation


Sometimes equations of a higher degree than second can be solved by reducing them to quadratic equations.
We shall consider some important types of such equations.
Examples
Solve the following reducing them to a quadratic equation.
1. 4x 4 − 25x 2 + 36 = 0
Solution
4x 4 − 25x 2 + 36 = 0 … (A)
Put x2 = m then (A) becomes
4m 2 − 25m + 36 = 0
4m 2 − 16m − 9m + 36 = 0
4m(m − 4) − 9(m − 4) = 0
(m − 4)(4m − 9) = 0
9
m = 4 or m =
4
9 3
x 2 = 4 ⇒ x = ±2 or x 2 = ⇒x=±
4 2
3 3

2. 8x 2 − 8x 2
= 63
Solution
3 −3
8x 2 − 8.x 2 = 63
3
Put x 2 = m
8m − 8.m −1 − 63 = 0
8
8m − − 63 = 0
m
Multiplying throughout by m
8m 2 − 63m − 8 = 0
(8m + 1)(m − 8) = 0
1
m = 8 or m = −
8

89
FXB0BAMM

3
1
x2 = −
8
2
 1 1
x3 =  −  =
 8 64
1
∴ x= or
4
3
x2 = 8
x 3 = 82 = 64
x=4
1
∴ x = 4 or x =
4
2 x +1 x
3. 4.2 − 9.2 + 1 = 0
Solution
4.22 x +1 − 9.2 x + 1 = 0
⇒ 4.22x.21 − 9.2 x + 1 = 0
⇒ 8.2 2x − 9.2 x + 1 = 0 … (A)
Put 2x = m then (A) becomes
8.m 2 − 9m + 1 = 0
(8m − 1)(m − 1) = 0
1
m = or m = 1
8
1
i.e. 2 x = = 2 −3
8
x = −3 or
2 x = 1 = .20
x=0
∴ x = 0 or x = −3
x 1− x 1
4. + =2
1− x x 6
Solution
x 1− x 1
+ =2 … (A)
1− x x 6
x 1 13
Put = m then (A) becomes m + =
1− x m 6
multiplying by 6m throughout, we get
6m 2 − 13m + 6 = 0
(2m − 3)(3m − 2) = 0
3 2
m = or m =
2 3
x 3 x 2
i.e. = or =
1− x 2 1-x 3

90
FXB0BAMM

x 9
=
1− x 4
9 − 9x = 4x
13x = 9
9 x 2 x 4
x= or = ⇒ =
13 1− x 3 1− x 9
9x = 4 − 4x
13x = 4
4 4 9
x= and hence x = or
13 13 13

Theory of quadratic equation


A quadratic equation can not have more than two roots. The standard quadratic equation is ax 2 + bx + c = 0 .
If possible, let the equation ax 2 + bx + c = 0 have three different roots, α, β and γ. Since they satisfy the
equation, we have
aα2 + bα + c = 0 ... (1)
2
a β + bβ + c = 0 ... (2)
a γ 2 + bγ + c = 0 ... (3)
Subtracting (2) from (1) we have
a ( α2 − β 2 ) + b(α − β) = 0
or (α − β) [ a(α + β + b) ] = 0
Therefore either α − β = 0 or a ( α + β ) + b = 0
But α − β cannot be zero as α and β are different.
a( α + β) + b = 0 … (4)
Similarly, using (2) and (3), we get
a (β + γ ) + b = 0 … (5)
Subtracting (5) from (4)
a( α − γ ) = 0 … (6)
Therefore either a = 0 or α – γ = 0. But ‘a’ is not equal to zero, also α − γ is not equal to zero as α and γ are
different. Therefore our assumption is wrong. Hence a quadratic equation cannot have more than two roots.

Nature of the roots of a quadratic equation


− b ± b2 − 4ac
We know that the quadratic equation, ax 2 + bx + c = 0 has roots . The nature of the roots
2a
depends upon the expression b2 − 4ac under radical sign, called discriminant. The following facts are quite
obvious.
1. If b2 − 4ac = 0 , then roots are real, rational and equal.
2. If b2 − 4ac is positive and a perfect square, roots are real, unequal and rational.
3. If b2 − 4ac is positive and not a perfect square, then the roots are real, irrational and unequal.
4. If b2 − 4ac is negative then roots are (not real) imaginary and unequal.

91
FXB0BAMM

Example 1
Find the nature of the roots of x 2 − 5x − 2 = 0
Solution:
The discriminant, b2 − 4ac = ( −5)2 − 4( −2) = 33
Therefore, roots are real, unequal and irrational.

Example 2
For what value of m will the equation x 2 + mx − ( m 2 + 3m − 32 ) = 0 have equal roots?
Solution
The discriminant, b2 − 4ac
= m 2 + 4 ( m 2 + 3m − 32 )
= 5m 2 + 12m − 128
Since the roots are equal, the discriminant should be zero.
∴ 5m 2 + 12m − 128 = 0
−12 ± 144 + 2560
∴m =
2×5
−12 ± 2704 −12 ± 52
= =
2×5 10
i.e. m = 4 or – 6.4

Problems leading to quadratic equations


1. Find two even positive consecutive integers whose product is 288.
Note:
(i) Any general even number is 2n
(ii) Any general odd number is 2n + 1 or 2n – 1
Solution
Let the two consecutive positive even integers be 2n and 2n + 2
Their product is 2n(2n + 2)
As per the problem
2n(2n + 2) = 288
n(2n + 2) = 144
n(n + 1) = 72
n 2 + n − 72 = 0
(n + 9)(n − 8) = 0
Therefore, n = 8 or – 9
Ignoring – 9, the first even number is 2n = 16;
next even number is 2n + 2 = 16 + 2 = 18
2. Find the length and breadth of a rectangular field, whose perimeter is 40 m and area is 96 sq. metres.
Solution
Let x be the breadth and y be the length
The area is x.y and the perimeter 2(x + y) as per the problem,

92
FXB0BAMM

2(x + y) = 40
x + y = 20
x = (20 − y)
Area (20 − y).y = 96
20y − y 2 = 96
y 2 − 20y + 96 = 0
i.e. (y − 8)(y − 12) = 0
y = 8 or 12
If its length is 12, breadth is x = 20 – 12 = 8
If length is 8, then breadth x = 20 – 8 = 12 which is not applicable as length is smaller than breadth.
Therefore, the length is 12 m and breadth is 8 m
3. The digit in the ten’s place of a two digit number is equal to the square of the digit in unit’s place.
If 54 is subtracted from that number, its digits are interchanged. Find the number.
Solution
Let the digit in the unit’s place be x.
Then as given in the problem the ten’s place will be x2
∴ The number = 10x2 + x
If the digits are interchanged, the new number will be 10x + x2
As per the given condition
(10x 2 + x) − 54 = 10x + x 2
9x 2 − 9x − 54 = 0
x2 – x – 6 = 0
Simplifying, we get
∴ (x − 3)(x + 2) = 0
∴ x = 3 or x = −2
Rejecting the negative value we have x = 3
Therefore the two digit number 10x2 + x
= 10 × 32 + 3
= 90 + 3 = 93
4. The product of four consecutive natural numbers is 360. Find the numbers.
Solution
Let the four consecutive natural numbers be x, x + 1, x + 2, x + 3
The product x(x + 1)(x + 2)(x + 3) = 360
(x 2
+ 3x ) ( x 2 + 3x + 2 ) = 360 ... (A)
Put x 2 + 3x = m. Then (A) becomes
m(m + 2) − 360 = 0
m 2 + 2m − 360 = 0
m 2 + 20m − 18m − 360 = 0
(m + 20)(m − 18) = 0
m = −20 or m = 18
x2 + 3x – 18 = 0 … (1)
x2 + 3x + 20 = 0 … (2)

93
FXB0BAMM

Using (1) (x + 6)(x − 3) = 0


x = 3 or x = −6
Roots of (2) are not real as
b2 – 4ac = 9 – 80 = – 79 is negative. As numbers are natural x ≠ –6. Therefore, the required numbers are
3, 4, 5, 6.

Graphical method
Example 1
Solve 2x 2 − 5x − 12 = 0.
Let y represent the value of the expression.
Then, y = 2x 2 − 5x − 12 .
We tabulate the values of x and y as follows.
x 0 1 2 3 4 6 −1 −2 −4

y = 2x 2 0 2 8 18 32 72 2 8 32

−5x − 12 − 12 − 17 − 22 − 27 − 32 − 42 −7 −2 8

y = 2x 2
− 12 − 15 − 14 −9 0 30 −5 6 40
5x − 12

(0,−12) (1,−15) (2,−14) (3,−9) (4,0) (6, 30) (−1,−5) (−2, 6) (− 4, 40)

We plot the points (0, −12), (1, −15), (2, −14) ...... (−2, 6).
A free hand curve is drawn passing through all the points.

94
FXB0BAMM

To solve equation (1), we have to find values of x, which make 2x 2 − 5x − 12 = 0 , i.e. values of x which
make y = 0. Now when y = 0, the graph crosses the x-axis. In the figure we see that this graph crosses x-axis
at the points x = 4 and x = – 1.5.
Hence the roots are 4 and − 1.5.
Second method
The equation 2x 2 − 5x − 12 = 0 is the same as the equation 2x 2 = 5x + 12 .
Draw the graph of y = 2x2 (1) and y = 5x + 12 (2)
For (1)
x 2 3 –4 –2
y 8 18 32 +8
For (2)
x 0 1 +4 –1
y 12 17 32 7

The graphs intersect at the points P and Q. The values of x at the point P give the same value of y namely
MP for both the graphs i.e., x = OM. We have 2x2 = 5x + 12. Therefore x = OM = 4 is a solution of the
equation.
Similarly, x = ON = –1.5 is another solution of the equation. In other words, the abscissae of the points of
intersection of the graph y = 2x2 and y = 5x + 12, are the roots of the equation 2x2 = 5x + 12.
We conclude in general that we can find the roots of ax2 + bx + c = 0.
(a) By finding the abscissae of the points where the graph of the equation y = ax2 + bx + c crosses the x-axis
OR
(b) By finding the abscissae of the points of intersection of the graph of the equation.
y = ax2 … (1)
y = − bx − c … (2)

95
FXB0BAMM

Points to Ponder
A polynomial of degree 2, in variable x, in standard form ax2 + bx + c(a ≠ 0), when equated to zero is called
a Quadratic equation of variable x.
Standard form of a Quadratic Equation is ax2 + bx + c = 0; where a, b, c are real numbers but a ≠ 0.
Here ‘a’ and ‘b’ are the coefficients of x2 and x respectively. ‘c’ is called constant term.

Standard form of a quadratic equation


ax2 + bx + c = 0, a ≠ 0 and b, c ∈ R
Special cases
(i) If b, c = 0, then ax2 = 0,
0
⇒ x2 = = 0
a
⇒ x = 0, 0
(ii) If b = 0, then ax2 + c = 0,
−c −c
⇒ x2 = , ⇒x=±
a a
(iii) If c = 0, then ax2 + bx = 0,
⇒ x(ax + b) = 0,
b
⇒ x = 0, −
a

Solution of a quadratic equation


1. Factorisation
2. Method of completing the square:
Consider the quadratic equation, ax2 + bx + c = 0;
2
 b  b2 − 4ac
⇒ x +  =
 2a  4a 2
3. Using the formula:
In the method second, we see that solutions / roots of the quadratic equation ax2 + bx + c = 0
− b ± b 2 − 4ac
(a ≠ 0) by completing the square, x = .
2a

Nature of roots
Quadratic equation: ax2 + bx + c = 0 (a ≠ 0) value of (b2 − 4ac) is called discriminant of the quadratic
equation. The value of (b2 − 4ac) is denoted by D.
∴ D = b2 − 4ac
The discriminant plays an important role in finding the nature of the roots of the quadratic equation.
(i) If D = 0, then roots are real and equal.
(ii) If D > 0, then roots are real and unequal.
(iii) If D < 0, then roots are not real.

96
FXB0BAMM

Sum and product of roots


If α and β are the roots of quadratic equation ax2 + bx + c = 0, then
−b Coefficient of x
(i) Sum of roots, α + β = =−
a Coefficient of x 2
c constant term
(ii) Product of roots, αβ = =
a coefficient of x 2

Relation between roots and coefficients


If roots of quadratic equation ax2 + bx + c = 0 (a ≠ 0) are α and β.
2 b2 − 4ac D
(i) α − β = (α + β) − 4αβ = =
a a
2
2 b − 2ac
(ii) α2 + β2 = ( α + β ) − 2αβ =
a2

97
FXB0BAMM

98

You might also like